Criminal Law Reform Policy in Efforts to Overcome Corruption Crimes Committed by Regional Officials - Marthinus - Mambaya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
The aim of the normative research currently being carried out is to find out how the implementation of efforts to overcome criminal acts of corruption committed by regional officials. Corruption is a threat to the principles of democracy which uphold transparency, accountability and integrity, as well as the security and stability of the Indonesian nation.  The research method used is descriptive analysis which leads to normative juridical legal research, namely research carried out by referring to legal norms, namely researching library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The research results show that legal efforts to eradicate criminal acts of corruption committed by regional officials can be carried out in two strategies, namely preventive and repressive efforts. And community participation must fully support all Government policies, especially in law enforcement efforts in the context of overcoming criminal acts of corruption committed by regional officials.